2016
DOI: 10.1167/iovs.16-20106
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Small Vessel Disease in Branch Retinal Artery Occlusion

Abstract: Patients with BRAO showed different cerebrovascular characteristics following retinal emboli, including brain MRI findings. The results suggest that we must consider SVD etiology as well as large vessel disease mechanisms in the pathophysiology of BRAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…As in other studies, arterial hypertension was the most frequently identified risk factor, found in 84.7% of RAO patients [ 4 , 6 , 10 , 11 , 12 , 13 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…As in other studies, arterial hypertension was the most frequently identified risk factor, found in 84.7% of RAO patients [ 4 , 6 , 10 , 11 , 12 , 13 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 70%
“…The characteristic risk factors for CRAO and BRAO are nearly identical to those for ischemic stroke, with hypertension being the most common risk factor for both CRAO and BRAO [ 1 , 2 , 3 , 4 , 6 , 10 , 11 , 12 , 13 , 14 , 15 ]. Similar to patients with stroke, patients with RAO are at high risk of subsequent cardiovascular events [ 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed descriptions of the MRI protocols and SVD findings on the brain MRIs were published in our previous studies. [11, 12] Briefly, MRI protocols included T1-weighted, T2-weighted, T2* gradient-recalled echo (GRE), diffusion-weighted, and fluid-attenuated inversion recovery (FLAIR) images. WMH were defined as areas of bright, high-signal intensities noted on T2-weighted images and graded by Fazekas score.…”
Section: Methodsmentioning
confidence: 99%
“…Another earlier finding suggested that WMHs are associated with HIV seropositive individuals [ 160 ]. Recently, during investigation of the BRAO, it was suggested that small vessel etiology may play a pivotal role in pathophysiology of BRAO [ 161 ]. The above investigations give another dimension of cSVD research and exploration in the direction of linkage to several other non-cerebral disorders.…”
Section: Cerebral Small Vessel Disease Associated Diseasesmentioning
confidence: 99%